Biochemistry laboratory manual for undergraduates : an inquiry-based approach - Gerczei, Timea; Pattison, Scott, 1947- (De Gruyter Open, 2014)
Biochemistry Laboratory Manual for undergraduates is the first textbook on the market that uses a highly relevant model, antibiotic resistance, to teach seminal topics of biochemistry and molecular biology. Inclusion of a research project does not entail a limitation: this manual includes all classic biochemistry techniques such as HPLC or enzyme kinetics and is complete with numerous problem sets relating to each topic.